Szadek jako ośrodek sukienniczy w XV–XVII wieku - Marszał, Tadeusz (Biuletyn Szadkowski, 2014)
In 15th and 16th centuries, Szadek, like many other Polish towns, was undergoing a period of intensive growth and prosperity. Many craftsmen, also from abroad, carne and settled in Szadek in 15th century. The town became an important wool cloth manufacturing centre on the economic map of Poland, surpassed only by Brzeziny in the Sieradz and Łęczyca district and a few other towns. The growth of wool cloth manufacturing spurred the development of other crafts, such as brewing, tailoring, shoemaking, furriery, carpentry and flour-milling, and trade. The economic position of Szadek was reflected in its administrative, judicial, cultural, political and social functions. In 15th-16th centuries the town was as important as such major urban centres of that time as Sieradz or Wieluń. The beginning of 17th century was a period of Szadek's degradation and decline of its cloth production, which had two main causes. The first one was a series of misfortunes that affiicted this town in turbulent 17th century: fi.res, epidemics and passages of troops connected with wars. The second reason was the structure of wool manufacturing in Szadek, oriented to meeting local demand and mass production of cheap, inferior kind of coarse cloth, mainly bought by peasants. Impoverished rural population in 17th century bought less and less woollen cloth made in towns. Decreased demand was also caused by development of cloth manufacture in rural areas of southem and eastern Greater Poland. The shrinking demand on intemal market for cloth manufactured in Szadek led to the decline of this town's two-centuries long period of prosperity.